Multimodalitas dalam unggahan di Twitter yang dianggap mengandung pelecehan seksual - Fitri Amalia; Suhandano Suhandano (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
Research in linguistics related to sexual harassment on social media is still very limited. The research found was limited to analysis in the form of verbal text, without visual material. This study is needed in the field of linguistics, especially forensic linguistics. To respond to these conditions, a study is needed that can assist efforts to examine language data academically in linguistics. This study aims to discuss the relationship between verbal and visual modes in Twitter posts that are considered to contain sexual harassment. The method used in this study was qualitative methods with two data collection techniques, namely listening and recording. The data in this study is in the form of screenshots of uploads sourced from Twitter with indications of sexual harassment. The analytical tool used in this study is Halliday's SFL theory to analyze verbal modes and Kress &Van Leeuwen's visual grammar theory to analyze visual modes. The results showed that the verbal and visual modes in the upload become a unity of elements that build meaning. Both work together to convey a related message, namely the existence of sexual harassment. The analysis and results of this study are expected to be a reference in forensic linguistic studies.